Tax knowledge and tax compliance determinants : evidence of value added tax (VAT) in Thailand - Ranchida, Sangduang (2016)
This study examined the Value Added Tax (VAT) knowledge and the understanding of the Small and Medium Enterprises (SMEs) entrepreneurs who registered for VAT and investigated the determinants of VAT payers’ compliance levels. VAT is a significant source of the Thai government’s revenue. However, very little research has been done in investigating the problem of uncollected VAT. Two survey data were used in this study. The first survey focused on VAT knowledge and the understanding of the entrepreneurs of the VAT-registered SMEs. The second survey explored the determinant variables which affect VAT compliance of VAT-registered SMEs. In each case 1,000 mail questionnaires were used. The survey response rate of the individual VAT-registered SMEs was 30.9% and 31.6% was the response rate of the VAT-registered SMEs. The results of the t-test and ANOVA indicated that there were significant mean differences of VAT knowledge and understanding among the characteristics of the participants. The result of multiple regressions showed that record- keeping, tax rate, understanding tax law, complexity, probability of detection, and business ethics strongly influenced VAT compliance of the VAT-registered SMEs. It also gained further insight into some problems and barriers faced by the entrepreneurs of those VAT-registered SMEs. The results of this study could inform policy-makers in Thailand and elsewhere to enhance the knowledge of VAT for entrepreneurs of VAT-registered SMEs. It can also serve as an indicator for tax administrators to pay attention to the importance of VAT knowledge by designing the appropriate VAT education mechanism (i.e. brochures, websites, and other media) and to disseminate knowledge and understanding between the tax authorities and the taxpayers. Besides, the results of the study also provide specific insights of key variables that significantly associate with VAT compliance that can enable tax administrators to implement appropriate strategies to increase VAT compliance and VAT collection.